Re-adenylation by TENT5A enhances efficacy of SARS-CoV-2 mRNA vaccines - Paweł S. Krawczyk; Michał Mazur; Wiktoria Orzeł; Olga Gewartowska; Sebastian Jeleń; Wiktor Antczak; Karolina Kasztelan; Aleksandra Brouze; Katarzyna Matylla-Kulińska; Natalia Gumińska; Bartosz Tarkowski; Ewelina P. Owczarek; et al. (Nature, 2025)
Abstract Despite the widespread use of mRNA vaccines against COVID-19, little is known about the metabolism of therapeutic RNAs. Here we use nanopore sequencing 1–3 to analyse individual therapeutic mRNA molecules, focusing on their poly(A) tails. We show that the Moderna mRNA-1273 vaccine 4 has a poly(A) tail of around 100 nucleotides, followed by an mΨCmΨAG sequence. In cell lines, mRNA-1273 undergoes rapid degradation initiated by mΨCmΨAG removal, followed by CCR4–NOT-mediated deadenylation. However, in medically relevant preclinical models, particularly in macrophages, mRNA-1273 poly(A) tails are extended to up to 200 nucleotides by the TENT5A poly(A) polymerase 5–7 , which is induced by the vaccine. Re-adenylation, which stabilizes target mRNAs, is consistently observed in synthetic mRNAs that encode proteins targeted to the endoplasmic reticulum, such as ovalbumin or antigens from Zika virus 8 or the malaria parasite 9 . The extent of re-adenylation varies: the BioNTech–Pfizer BNT162b2 vaccine 10 shows less potent re-adenylation than mRNA-1273, which correlates with a smaller proportion of membrane-associated BNT162b2. This highlights the crucial role of spatial accessibility to ER-resident TENT5A in determining re-adenylation efficiency. In vivo, TENT5A is expressed in immune cells that take up mRNA vaccine, and TENT5A deficiency reduces specific immunoglobulin production for mRNA vaccines after immunization in mice. Overall, our findings reveal a principle for enhancing the efficacy of therapeutic mRNAs, paving the way for improvement.